Pemberantasan Terhadap Penyalahguna Narkotika Yang Dilakukan Oleh Remaja Di Wilayah Hukum Kepolisian Resor Kampar - Ginting, Bayudwi Putra; Firdaus, Firdaus; Ferawati, Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Crime which is currently the most frequently encountered problem in people's lives is the problemof drug abuse and circulation. This condition is very worrying because the victims of drug abuse areteenagers where when children and adolescents are damaged by narcotics, their future is destroyed andendanger the nation's next generation. For this reason, the role of the Police is needed to eradicateadolescent drug abuse so that there will be no more abuse and circulation of narcotics in the jurisdiction ofthe Kampar Resort Police.This type of research can be classified as sociological, because in this study the author directlyconducts research on the location or place under study in order to provide a complete and clear picture ofthe problem under study. This research was conducted at the Kampar Resort Police, while the populationand samples were all parties related to the problems examined in this study, data sources used primarydata, secondary data, and tertiary data, data collection techniques in this study by observation, interviews ,questionnaire, and literature study.From the results of the study, it can be concluded that Sat Narcotics in Kampar District Police arealways consistent in terms of law enforcement both from Preventive and Refractive Measures. Second,Suggestions from the author First, Memorize and improve the performance of the Drug Investigation Unit,so that narcotics abusers can be eradicated. Second, legal counseling activities carried out by the NarcoticsInvestigation Unit with the District Narcotics Agency to be further improvedKeywords: Eradication - Teenagers - Abusers - Narcotics